Nurse's interventions in preventing falls in hospitalized children: scoping review - Alexandra Margarida Ribeiro Brás; Margarida Maria de Sousa Lourenço Quitério; Elisabete Maria Garcia Teles Nunes (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: map both nursing interventions for the prevention of falls in paediatric age during hospitalization and the instruments for assessing the risk of falls in paediatrics. Methods: scoping review according to the protocol of Joanna Briggs Institute, with acronym PCC (P - children, C - fall preventive nursing interventions and instruments for assessing the risk of falling, C - hospital admission), in three sources of information (EBSCO, PubMed and SciELO). Results: the sample consisted of seven articles. The education of the child/family is the basis of the interventions, and the instruments for assessing the risk of falling identified were: Humpty Dumpty Falls Scale, GRAF PIF, CUMMINGS, I'M SAFE and CHAMPS. Conclusions: the education of children/parents on preventive measures is important and should be reinforced during hospitalization, using different methodologies. The Humpty Dumpty Falls Scale was the most analyzed.